Cytomorphometric Neutrophil and Monocyte Markers May Strengthen the Diagnosis of Sepsis. (December 2018) - Mammen, Joy; Choudhuri, Jui; Paul, Joshua; Sudarsan, Thomas Isaiah; Josephine, T.; Mahasampath, Gowri; Jeyaseelan, Vishali; Nair, Sukesh C.; Peter, John Victor
Background: The diagnosis of sepsis is challenging in the absence of a gold standard test. Recent studies have explored the role of neutrophil and monocyte volume, conductivity, and scatter (VCS), derived from automated hematology analyzers, in diagnosing sepsis. We assessed the diagnostic accuracy of VCS parameters in critically ill patients with sepsis. Methodology: In this prospective study, VCS parameters, procalcitonin, and C-reactive protein (CRP) were assessed in patients with proven sepsis (cases) and 2 control groups (intensive care unit [ICU] patients without sepsis and healthy blood donors). The diagnostic property of each test was explored by calculating sensitivity, specificity, negative and positive predictive values, and area under the curve (AUC). Results: The study included 65 patients with sepsis, 58 nonseptic ICU controls, and 98 blood donors. Procalcitonin and CRP were not significantly different ( P > .06) between patients with sepsis and nonseptic patients. Mean (95% confidence interval [CI]) neutrophil volume (MNV) was significantly higher ( P < .001) in patients with sepsis (165.5; 95%CI 161.6-169.4) than in nonseptic (157.3; 95%CI 154.6-160.1) patients and donors (148.9; 95%CI 147.9-150). A similar pattern was seen with mean monocyte volume (MMoV). Neutrophil and monocyte conductivity and scatter parameters were variably associated. The AUC was highest for MMoV (0.74) and lowest for CRP (0.62). Among all parameters, MNV and MMoV had the highest specificity of 85% and 80%, respectively. Conclusion: In critically ill patients with suspected sepsis, VCS parameters may help strengthen the diagnostic probability of sepsis. Future studies may explore the role of serial monitoring of VCS to track response to antimicrobial therapy.